Sources of Stress among Saudi Arabian Nursing Students: A Cross-Sectional Study - Wafaa Aljohani (MDPI AG, 2021)
Introduction: Nursing students experience higher levels of stress than those in other health-related disciplines; however, there are limited data exploring stress among these students in a Saudi context. Aim: This study examines sources of stress among nursing students at an academic institution in Jeddah, Saudi Arabia, using a descriptive quantitative cross-sectional research design. Methods: Data were collected from a convenience sample of 500 undergraduate nursing students, with a response rate of 71.8%, using an adapted Stress in Nursing Students (SINS) questionnaire. Results: Nursing student sources of stress fell into three categories: academic concerns, clinical practice, and social factors. Discussion: The results demonstrate commonality between other countries’ sources of stress for nursing students but highlight cultural factors unique to Saudi Arabia. This study shows opportunities for cross-cultural learning and areas needing cultural tailoring to reduce stress among nursing students.